TINJAUAN YURIDIS PEMBATALAN PERATURAN DAERAH KOTA YOGYAKARTA DENGAN KEPUTUSAN GUBERNUR DAERAH ISTIMEWA YOGYAKARTA - Ziko Ostaki; Francisca Romana Harjiyatni; Sri Handayani Retna Wardani (Kajian Hasil Penelitian Hukum, 2018)
The position of the Governor's Decree in the hierarchy of laws and regulations in Article 7 of Law number 12 of 2011 on the Establishment of Laws and Regulations is not included in it, but the position of the Governor's Decree is a form of Governor's action in exercising administrative authority. This means that the validity of the Decree of the Governor in the conduct of the legal Regional Arrangement insofar as it is governed by law, it is based on Article 87 of Law number30 Year 2014 on Government Administration, however, the cancellation of regional land use using the Governor's Decree shows that the distribution of power in Indonesia is not working, this is because according to Article 251 of Law number23 of 2014 on Regional Government states that if in the process of cancellation of the regional regulation there is an objection, then submitted through the Minister of Home Affairs. The process thus shows that the government is not running properly, then the ideal concept in the cancellation of local regulations in return again to the judicial institution according to its functions and duties under Article 24A of the 1945 Constitution of the State of the Republic of Indonesia.Keywords: Regulation Cancellation, Governor's Decision, Authority